Child poverty in Malaysia: What do Malaysians think? / Norhaslinda Jamaiudin and Maziah Mahmud - Jamaiudin, Norhaslinda; Mahmud, Maziah (2021)
Child poverty is an emerging issue in Malaysia. A study conducted by UNICEF in 2018 reveals that 11 percent of children in Malaysia living in urban poverty with 15 percent of children below the age of five are underweight, 22 percent of the children are stunted and only 50% of 5- to 6-year-olds attend pre-school enrolment (UNICEF, 2018). It is truly staggering to think that many of our children lived in poverty. Children who are living in poor households with limited access to nutritious food and education experienced a real deterioration in their living standards. They are vulnerable to many possibilities including material and social deprivation. Poor children have many needs, but money matters the most. In most cases, those needs are often left unattended due to poor parental and household characteristics (Lindquist & Lindquist, 2010; Chou, 2013; Saunders, Brown, Bedfood, & Naidoo, 2019). Coming from unfortunate family backgrounds, many of these children suffer material hardship and underachievement in school (Madrick, 2020). According to the report, the number of registered students in school decreased despite the increasing number of children in the current population (Joseph Chin, 2017). This is a worrisome situation as deprivation in life could lead to many problems including underachievement, illiteracy, juvenile delinquency, and many others (UNICEF, 2018). Poor living condition indeed has taken a toll on the lives of children, thus limits their life opportunities in all aspects.